Transformation of O.Myshuga’s Singing School’s Principles into his Pupils’ Creative and Pedagogical Activity (S.Myrovych) - Tsaruk, Svitlana (Pedagogical Discourse, 2014)
The main stages of the creative way of the prominent singer, vocal pedagogue Sofiia Mykhailivna Myrovych in close connection with the life principles and views of her teacher Oleksandr Myshuga have been reflected in the article. From the reminiscences of S.Myrovych herself, her pupils and archive materials, which we found, there was an attempt to study the influence, done by Myshuga as a personality, as an artist, as a singer, as an author of the system of voice-training onto establishment and formation of Sofiia Myrovych – singer and pedagogue. The article has the proofs of successful activity of Sofiia Myrovych – owner of coloratura soprano, who during many years was singing on the best theatrical stages of our country and who had great success in teaching young singers. Methodological advices of professor Sofiia Myrovych have been found, They were published in one of the scientific issues of Leningrad N.Rimsky-Korsakov State conservatoire in 1940. Their analysis was done from the position of taking into account by the pedagogue the main regulations of the system of teaching singing of Oleksandr Myshuga. Thus, the importance of the contribution of the pupil of Ukrainian professor Oleksandr Pylypovych Myshuga into the development of Russian vocal art has been documentary confirmed.